PENGARUH PENERAPAN STRATEGI BELAJAR PQ4R (PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW) MENGGUNAKAN MEDIA KOMIK PADA KEMAMPUAN KOGNITIF SISWA PADA MATERI SISTEM SARAF - Lia Agustina; Rida Oktorida Khastini; Siti Gia S. Fitri (Universitas Sultan Ageng Tirtayasa, 2015)
This research aimed to determine the effect of PQ4R learning strategy using comic media on students interest and cognitive ability toward the nervous system concept. The method was a quasi-experimental desain with randomized control group pretest posttest. PQ4R learning strategy using comic media was as independent variables, and cognitive abilities was as dependent variables. Population in this research were all of students classXIIPA1Ciomas High School, academic year 2012-2013. Overall subject of population was used as the sample of research.Sample class XI IPA 1 as an experiment class and XI IPA 2 as a control class. Sampling technique used random sampling. Instrument used were multiple choice test for determining students cognitive ability, observation sheets and documentation. All the instrument, were analyzed by t testfor hypothesis.The resultof hypothesis showed the influence of PQ4R learning strategyusingcomic media on students interest, cognitive ability